Pengembangan Manajemen Strategis dengan Kajian dalam Knowledge Externalization - Augustina Asih Rumanti (Jurnal METRIS, 2014)
Small and Medium Enterprises (SMEs) hold an important role in developing a country’s economy.Nevertheless, data shows that SMEs didn’t manage to stay in the competition due to the a handful ofproblems. Human resources that run these SMEs become substancial. With their knowledge, human resourceplanning the purpose of establishing the SMEs, creating a wide range of products as well as providing anyservices to customers. Knowledge of each individual that run this business is certainly different, despitehaving the same profession. This difference may appear because of the tacit knowledge possessed by each ofthese individuals. Mastery of explicit knowledge may afford to produce a uniformity, but understanding tacitknowledge is able to produce something more valuable. Tacit knowledge will provide a more tangible impactwhen externalized into explicit knowledge that is more easily understood, and further documented and takeninto deliberation in developing strategies to achieve and maintain the earmark of the SME.Case study is conducted in So Kressh CV. Kajeye Food, a medium enterprise in Malang producing variouskind of fruit chips. The result shows that knowledge externalization only affect the human resources in SoKressh. After that, conducted by making the manual book with the working method as an item that canrepresent the existence of knowledge externalization. And for the last step is planning the human resourcedevelopment strategies that focuses on : an effective and efficient working methods, an effectivecommunication, a two-way concept in delivering the training materials, making a training simulation andsocializing the program.